Effect interaction between irrigation interval, GA3 and Kimon -24 organic fertilizer in some physiological parameters of spinach ( Spinacia oleracea L.) - A. A. Yaseen; S. M. Kadim (Al-Qadisiyah Journal of Pure Science, 2017)
The present experiment was conducted during winter season in (2011 – 2012) on clay-silty soil. The goal of the experiment was to find the effect of irrigation period , foliar application of growth regulators GA3 and the organic liquid fertilizer Kimon -24 on parameters mineral content of spinach Spinacea oleracea L., and its content of Oxalic acid(OA).The design of the experiment was randomized complete blocks (RCBD) in a split-split plot arrangement with three replications. The main plot was three irrigation periods, (2, 4 and 6 day), the sub – plot was four concentrations of GA3 (0, 200, 400 and 600 mg.L-1), while the sub-sub plot was two concentrations of the organic liquid fertilizer Kimon- 24 (0 and 20 ml.L-1). The Last Significant Difference (LSD) at 0.05 probability level was used to compare treatments means, whenever treatment effects were evident.Irrigation period and GA3 and applied and organic liquid fertilizer Kimollin 24 when was applied. Only organic liquid fertilizer Kimon- 24applied after 15 day of the first application. The following parameters were measured 30 days after treatment. The percentage of nutrient in leaf N, P, K, Mg and measured as well as leaves content of minerals nutrients (Fe and Ca) in addition to (OA). Results showed: The 2-day interval irrigation increased content of the percentage of N, P, K, Mg in the leaf and leaves content of minerals (Fe and Ca). The treatment 6-day irrigation interval which caused decreasing an (OA).The use of GA3 (200mg.L-1) reduced of (OA)content. The concentration of GA3 400mg.L-1increased leaves content of the percentage of N, K , Mg and Fe. Concentration 20 ml.L-1 of Kimon-24 gave significant increase in all parameters study and gave less leaf content of (OA).The interaction between irrigation period and GA3 had significant influence on all growth parameters. The treatment of 6-day irrigation interval with (200mg.L-1 ) of GA3 caused reduced (OA). The treatment irrigation period of 2-day with 400mg.L-1 GA3 gave higher percentage of N, P, K,Mg and leaf content of Fe. The interaction between irrigation period and Kimon-24 had varied significant influence on quality parameters. The irrigation interval of 2-day Kimon-24 increase percentage of N, P, K, Mg , leaf content of Fe and Ca. The interaction between GA3 and Kimon- 24 had significant influence on most studied parameters. The Concentration of GA3 200mg.L-1 with the use of Kimon-24 gave less (OA)content in the leaf.The interaction between the three factors included in the experiment revealed a significant effect on all parameters studied.